Composite carbon-coated graphite negative electrode material and preparation method and application thereof
By using composite carbon cladding on graphite anode material, the uniform distribution of graphitized carbon and hard carbon increases the number of lithium embedded active sites, and controls the cladding structure to reduce high-temperature side reactions, the graphite anode material is solved in a fast manner The balance between charging and high-temperature performance achieves excellent fast charging performance and high-temperature stability of the material.
Patent Information
- Application Number
- CN202411591266.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
While improving fast charging performance, existing graphite negative electrode materials are difficult to maintain high-temperature performance, and are prone to side reactions with the electrolyte, resulting in capacity loss.
The graphite negative electrode material is coated with composite carbon, and the composite carbon layer composed of graphitized carbon and hard carbon is coated on the outer surface of the graphite core. The uniformly distributed hard carbon and graphitized carbon increase the number of lithium-embedded active sites of the material, and By controlling the structure and composition of the cladding layer, the occurrence of side reactions at high temperatures is reduced.
The fast charging performance and high-temperature performance of graphite negative electrode materials are achieved, the fast charging capability of the material is improved, and side reactions are reduced at high temperatures, maintaining the high-temperature stability and capacity recovery rate of the battery.
Smart Images

Figure CN119480972A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field related to batteries, and in particular relates to a composite carbon-coated graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] Since the birth of lithium secondary batteries in the 1990s, after more than 30 years of development, lithium secondary batteries have been widely used in various fields of society and have become the most popular energy storage device. Among the optional lithium-ion battery negative electrode materials, graphite negative electrode materials occupy more than 90% of the lithium-ion battery negative electrode material market share due to their advantages such as strong electronic conductivity, stable charge and discharge platform, small lithium insertion expansion, good structural stability, and economic and environmental protection. It is the first choice for lithium-ion battery negative electrode materials.
[0003] Although graphite has many of the advantages mentioned above, its fast charging performance is poor, and this feature has become one of the main factors limiting the charging capacity of lithium-ion batteries. The poor fast charging performance of graphite is mainly attributed to its unique structural characteristics. First, the interlayer spacing of graphite crystals is only 0.336nm. Due to the narrow interlayer spacing, the diffusion rate of lithium ions between graphite is slow. Secondly, the graphite surface is an anisotropic structure, with fewer active sites for lithium ion embedding, and there are certain limitations on the charge transfer of lithium ions on the graphite surface. In order to improve the fast charging ability of graphite, amorphous carbon coating is usually used to modify the surface of graphite. Although this modification method can make the material's rate performance and first coulomb efficiency better than uncoated graphite, the high proportion of amorphous carbon is prone to side reactions with the electrolyte at high temperatures, resulting in irreversible capacity loss of the battery. Therefore, the high temperature performance of the material is poor.
[0004] Therefore, how to improve the high-temperature performance of graphite negative electrode materials while improving their fast charging performance is a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of the technical problem that existing graphite negative electrode materials cannot have both fast charging performance and high temperature performance, the present invention proposes a composite carbon-coated graphite negative electrode material and a preparation method and application thereof.
[0006] A first aspect of the present invention provides a negative electrode material, comprising a core and a coating layer coated on the outer surface of the core, wherein the core comprises graphite, and the coating layer comprises graphitized carbon and hard carbon, and the graphitized carbon and hard carbon are uniformly distributed.
[0007] The negative electrode material proposed in the present invention is a material that has both excellent fast charging performance and good high temperature performance by coating the outer surface of a graphite (artificial graphite-like material) inner core with a composite carbon composed of graphitized carbon and hard carbon, and the graphitized carbon and hard carbon are evenly distributed.
[0008] Specifically, the traditional artificial graphite negative electrode material is a highly crystallized graphite material, which belongs to a mixed crystal, and its surface has an anisotropic structure. The lithium insertion sites are mainly distributed in the end faces and defects, and there are few lithium insertion sites, which do not support the rapid charge transfer of lithium ions on the particle surface. The presence of hard carbon in the composite carbon coating layer of the present invention increases the active sites on the material surface for lithium ion embedding, and the fast charging performance is also better than that of traditional artificial graphite.
[0009] At the same time, carbon coating modification is an effective modification method for preparing fast-charging graphite negative electrode materials. Soft carbon or hard carbon is usually used to coat and modify graphite to make the graphite surface structure tend to be isotropic, thereby increasing the lithium insertion active sites on the graphite surface. However, while this method improves the fast charging ability of graphite, it also causes more side reactions between the material and the electrolyte at high temperatures, thereby reducing the high temperature performance of the material. The composite carbon coating layer structure of the present invention contains both hard carbon and graphitized carbon, and the graphitized carbon with an ordered structure and the hard carbon with a disordered structure are evenly distributed in the coating layer, which can effectively reduce the deterioration of the high temperature performance of the material while providing more lithium insertion active sites for the graphite surface.
[0010] In some embodiments of the present invention, the intensity ratio ID / IG of the Raman D peak and G peak of the coating layer satisfies the relationship: 0.15≤ID / IG≤0.7.
[0011] Specifically, in Raman spectroscopy analysis, D peak and G peak are two common characteristic peaks in carbon materials, which represent different structural information. Among them: D peak is related to structural defects or disorder in carbon materials; G peak is related to the degree of graphitization and structural order of carbon materials. The ID / IG ratio is the intensity ratio of the D peak and the G peak, and its size is used to reflect the relative degree of graphitization and disorder in carbon materials. The larger the ratio, the more structural defects or disorder there are in the material; conversely, it means that the material has a higher degree of graphitization and lower disorder.
[0012] After being coated with amorphous carbon, the graphite surface tends to be isotropic in structure, and the number of defects and end faces increases significantly. Correspondingly, the number of lithium-embedded active sites on the graphite surface also increases significantly, which is beneficial to the rapid charge transfer of lithium ions on the graphite surface, greatly improving the fast charging ability of the graphite negative electrode material. However, due to the increase in the number of defects and end faces, amorphous carbon coating will also intensify the side reactions between the graphite negative electrode material and the electrolyte, especially under high temperature conditions, the amorphous carbon-coated graphite negative electrode material will react rapidly with the electrolyte and generate a large amount of impurities, resulting in an increase in battery impedance and irreversible capacity loss. In order to reasonably control the number of end faces and defects of the composite carbon-coated graphite negative electrode material, the present invention achieves this by controlling the ratio of hard carbon and graphitized carbon in the composite carbon coating layer.
[0013] The study found that when the relationship between ID / IG satisfies 0.15≤ID / IG≤0.7, a balance between the fast charging performance and high temperature performance of the material can be achieved, providing sufficient active embedding sites for the graphite surface while reducing the number of end faces and defects. When there are too few hard carbon components in the composite carbon coating, too many graphitized carbon components, and the ID / IG of the composite carbon coating is lower than 0.15, there are too few active sites on the material surface for lithium ions to embed, and the charge transfer of lithium ions on the material surface is limited. Under high-rate charging conditions, lithium ions are prone to aggregate on the material surface and generate lithium dendrites, and the fast charging performance of the material is reduced. When there are too many hard carbon components in the composite carbon coating, too few graphitized carbon components, and the ID / IG of the composite carbon coating is higher than 0.7, there are more exposed end faces and defects on the material surface, and it is easy to have more side reactions with the electrolyte under high temperature conditions and generate impurities, resulting in irreversible capacity loss of the battery and reduced high temperature performance of the material.
[0014] In some embodiments of the present invention, the relationship between ID / IG satisfies: 0.3≤ID / IG≤0.6.
[0015] In some embodiments of the present invention, the relationship between ID / IG satisfies: 0.3≤ID / IG≤0.5, such as 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.43, 0.45, 0.47, 0.5, etc.
[0016] In some embodiments of the present invention, the graphite is selected from one or more of artificial graphite, flake graphite, earthy graphite, and mesophase carbon microbeads, preferably artificial graphite.
[0017] The second aspect of the present invention provides a method for preparing the above-mentioned negative electrode material, comprising the following steps:
[0018] (1) mixing graphite and epoxy asphalt to obtain a mixture;
[0019] (2) subjecting the mixture obtained in step (1) to carbonization treatment in an inert atmosphere to obtain carbon-coated graphite;
[0020] (3) The carbon-coated graphite obtained in step (2) is graphitized in an inert atmosphere to obtain the negative electrode material.
[0021] In the preparation process of the negative electrode material proposed in the present invention, epoxy asphalt is used as the coating agent raw material, and the resin-based components and asphalt components coexisting in the epoxy asphalt are utilized. After carbonization and graphitization treatment, a uniformly distributed hard carbon and graphitized carbon composite carbon coating layer is obtained. Compared with traditional hard carbon or soft carbon coating, it is more conducive to the fast charging performance and high temperature performance of the material.
[0022] Specifically, epoxy asphalt is a mixture obtained by complex chemical modification of epoxy resin, curing agent and matrix asphalt. Epoxy asphalt contains both resin-based components that can be pyrolyzed into hard carbon and asphalt-based components that can be pyrolyzed into soft carbon. It is an ideal raw material for preparing composite carbon coatings. Soft carbon and hard carbon have different crystallization behaviors during high-temperature graphitization. Under high temperatures above 2600°C, most of the carbon atoms in soft carbon will be arranged in order and gradually transform into graphite crystal structures. However, under high temperatures above 2600°C, only a small number of carbon atoms in hard carbon will evolve into graphite crystal structures, and most of the carbon atoms are still evenly distributed in the material in the form of amorphous carbon. The present invention uses epoxy asphalt as a coating agent. After high-temperature carbonization and high-temperature graphitization, the epoxy asphalt is pyrolyzed into graphitized carbon and hard carbon and coated on the graphite surface, forming a new surface structure on the graphite particles. Compared with the original graphite surface, on the one hand, due to the existence of the hard carbon structure, the new structure has more lithium insertion active sites on the surface and better fast charging performance; on the other hand, due to the existence of the graphitized carbon structure, the high temperature performance deterioration of the material is avoided and the high temperature performance is also enhanced.
[0023] In some embodiments of the present invention, in step (1), the epoxy asphalt is selected from one or more of water-based epoxy asphalt, cured asphalt, and solvent-free epoxy asphalt.
[0024] In some embodiments of the present invention, in step (1), the mass ratio of graphite to epoxy asphalt is 10:(0.5-3), such as 10:0.5, 10:1, 10:1.5, 10:2, 10:2.5, 10:3.
[0025] Specifically, the mass ratio of graphite and epoxy asphalt determines the thickness of the coating. The study found that the thickness of the coating has a great influence on the fast charging performance and high-temperature storage performance of the composite carbon-coated graphite negative electrode material. When the coating is too thin, the proportion of hard carbon components in the composite carbon-coated graphite is too small, and there are fewer active sites on the surface of the material for lithium ion embedding, and the fast charging performance also decreases; when the coating is too thick, the proportion of hard carbon components in the composite carbon-coated graphite is too large, and there are more side reactions between the composite carbon-coated graphite and the electrolyte under high temperature conditions, and the high-temperature performance decreases.
[0026] In some embodiments of the present invention, in step (2), the temperature of the carbonization treatment is 700-1500°C.
[0027] In some embodiments of the present invention, in step (2), the temperature of the carbonization treatment is 700-1200°C.
[0028] In some embodiments of the present invention, in step (2), the temperature of the carbonization treatment is 800-1000°C.
[0029] In some embodiments of the present invention, in step (2), the carbonization treatment time is 1-4 hours.
[0030] In some embodiments of the present invention, in step (2), the carbonization treatment time is 2-3 hours.
[0031] In some embodiments of the present invention, in step (2), the inert atmosphere is a nitrogen atmosphere or an argon atmosphere.
[0032] In some embodiments of the present invention, in step (3), the temperature of the graphitization treatment is 2600-3200°C.
[0033] In some embodiments of the present invention, in step (3), the temperature of the graphitization treatment is 2800-3000°C.
[0034] In some embodiments of the present invention, in step (3), the graphitization treatment time is 2-12 hours.
[0035] In some embodiments of the present invention, in step (3), the graphitization treatment time is 4-6 hours.
[0036] In some embodiments of the present invention, in step (3), the inert atmosphere is a nitrogen atmosphere or an argon atmosphere.
[0037] A third aspect of the present invention provides a negative electrode plate, wherein the raw material for preparing the negative electrode plate includes the above-mentioned negative electrode material, or includes the negative electrode material prepared by the above-mentioned preparation method.
[0038] Specifically, the negative electrode material proposed in the present invention has excellent fast charging performance and good high temperature performance. The negative electrode plate made of this negative electrode material is applied to lithium-ion batteries, which can reduce the lithium deposition area on the surface of the negative electrode plate and improve the fast charging performance. At the same time, the plate can maintain a high capacity recovery rate regardless of whether it is in a high temperature or low temperature environment, and is almost not significantly affected by temperature changes. Therefore, the battery made of this negative electrode plate has good high temperature stability and fast charging characteristics, and has broad prospects for industrial application.
[0039] In some embodiments of the present invention, the raw materials for preparing the negative electrode plate further include a negative electrode conductive agent and a negative electrode binder.
[0040] In some embodiments of the present invention, the negative electrode conductive agent can be selected from conventional conductive agents, and typical but non-limiting conductive agents are, for example, conductive carbon black (such as acetylene black, Super P, Super S, 350G or Ketjen black), conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15 or Ks-6), carbon fiber or carbon nanotubes. The conductive agent is to ensure that the electrode has good charge and discharge performance. When the pole piece is made, a certain amount of conductive material is usually added to collect microcurrents between active materials and between active materials and current collectors, so as to reduce the contact resistance of the electrode and accelerate the movement rate of electrons. At the same time, it can also effectively increase the migration rate of lithium ions in the electrode material, thereby improving the charge and discharge efficiency of the electrode.
[0041] In some embodiments of the present invention, the negative electrode binder includes one or more of sodium alginate, lithium alginate, polyacrylic acid, sodium carboxymethyl cellulose (CMC) or styrene-butadiene rubber (SBR), preferably CMC and SBR. Conventional negative electrode binders can be used without particular limitation, and are only exemplary.
[0042] In some embodiments of the present invention, the mass ratio of the negative electrode active material, the negative electrode conductive agent and the negative electrode binder is (90-95): (2-4): (2-8), such as 90:2:3, 90:2:4, 92:3:5, 94:2:3, 93:3:6, 95:2:3, 95:2:5 or 95:4:5, including but not limited to the listed values, and other values not listed in the numerical range are also applicable. The negative electrode sheet contains a certain proportion of conductive agent and binder, which is conducive to making the active material adhere well to the current collector when making the electrode sheet, thereby improving the charge and discharge efficiency of the negative electrode.
[0043] A fourth aspect of the present invention provides a secondary battery, which includes the negative electrode plate described above.
[0044] In some embodiments of the present invention, the secondary battery is a lithium ion battery.
[0045] Specifically, during the charging process of a lithium-ion battery, under the action of an external voltage, lithium ions are released from the positive electrode material and enter the electrolyte, migrate to the surface of the negative electrode material along with the electrolyte, and desolvate on the surface of the negative electrode material. Then, charge transfer occurs at the lithium insertion active sites on the surface of the negative electrode material, and finally the lithium ions are embedded in the negative electrode material particles.
[0046] When the external voltage is large, lithium ions will be quickly transferred to the surface of the negative electrode and aggregate on the surface of the negative electrode. At this time, lithium ions will undergo rapid charge transfer on the surface of the negative electrode material, but due to the limited number of lithium insertion active sites on the surface of the negative electrode material, when the charge transfer rate on the surface of the negative electrode material is lower than the aggregation rate of lithium ions, the lithium ion concentration on the surface of the negative electrode material will gradually increase. When the lithium ion concentration on the surface of the material reaches a certain order of magnitude, some lithium ions will directly obtain electrons from the surface of the negative electrode material and generate lithium dendrites, resulting in irreversible capacity loss and certain safety hazards. Therefore, from this perspective, the number of lithium insertion active sites on the surface of the negative electrode material plays a decisive role in the fast charging performance of the negative electrode material.
[0047] In order to increase the number of active lithium insertion sites on the surface of graphite negative electrode materials, amorphous carbon coating of graphite is usually used to modify the graphite surface to make it tend to be isotropic, and the number of defects and end faces increases significantly, thereby greatly improving the fast charging ability of graphite negative electrode materials. However, due to the increase in the number of defects and end faces, amorphous carbon coating will also intensify the side reactions between graphite negative electrode materials and electrolytes, especially under high temperature conditions, amorphous carbon-coated graphite negative electrode materials will react quickly with the electrolyte and generate a large amount of impurities, resulting in increased battery impedance and irreversible capacity loss.
[0048] In order to solve the above technical problems, the present invention proposes a graphite negative electrode material compositely coated with hard carbon and graphitized carbon. In the composite carbon coating layer of graphite, hard carbon and graphitized carbon are evenly distributed, which provides sufficient active lithium insertion sites for the graphite surface while reducing the number of end faces and defects, thereby ensuring the high temperature performance of the material. Therefore, the lithium-ion battery prepared using the negative electrode sheet prepared with the negative electrode material of the present invention also has excellent fast charging performance and high temperature performance.
[0049] In some embodiments of the present invention, the secondary battery further includes a positive electrode sheet.
[0050] In some embodiments of the present invention, the raw material for preparing the positive electrode plate includes a positive electrode active material. The positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, and lithium iron phosphate, preferably lithium nickel cobalt manganese oxide, such as NCM523.
[0051] In some embodiments of the present invention, the raw materials for preparing the positive electrode plate further include a positive electrode conductor and a positive electrode binder.
[0052] In some embodiments of the present invention, the positive electrode conductive agent can be a conventional conductive agent, such as conductive carbon black (such as acetylene black, Super P, Super S, 350G or Ketjen black), conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15 or Ks-6), carbon fiber or carbon nanotubes, preferably carbon nanotubes.
[0053] Conductive agents are used to ensure that the electrodes have good charge and discharge performance. A certain amount of conductive material is usually added during the production of the electrode sheet. It collects microcurrents between active materials and between active materials and current collectors to reduce the contact resistance of the electrodes and accelerate the movement rate of electrons. It can also effectively increase the migration rate of lithium ions in the electrode materials, thereby improving the charge and discharge efficiency of the electrodes. Conventional conductive agents in the field can be selected and added in conventional amounts without any restrictive provisions.
[0054] In some embodiments of the present invention, the positive electrode binder can be a conventional binder, such as a fluorine-based polymer and / or a synthetic rubber, and is further preferably polyvinyl fluoride, polyvinylidene fluoride (PVDF), polytetrafluoroethylene, styrene-butadiene rubber, fluorine-based rubber, ethylene propylene diene rubber, preferably PVDF.
[0055] In some embodiments of the present invention, the raw materials for preparing the positive electrode plate include positive electrode active materials, positive electrode conductive agents and positive electrode binders in a mass ratio of (90-95): (1-4): (2-6). The positive electrode material of the lithium-ion battery contains a certain proportion of conductive agents and binders, which is conducive to the active material being well attached to the current collector when making the plate, thereby improving the charge and discharge efficiency of the positive electrode. It can be 90:1:3, 90:2:4, 92:3:5, 93:3:4, 94:1:3, 94:2:4, 95:1:3, 95:2:5 or 95:4:5, including but not limited to the listed values. At the same time, other values not listed in the numerical range are also applicable.
[0056] In some embodiments of the present invention, the secondary battery further includes an electrolyte containing a lithium salt.
[0057] In some embodiments of the present invention, the lithium salt is preferably at least one of LiPF6, LiBF4, and LiTFSI. It can be any conventional lithium salt without particular limitation.
[0058] In some embodiments of the present invention, the solvent of the electrolyte includes propylene carbonate, ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, N,N-dimethylacetamide, fluoroethylene carbonate, methyl propionate, ethyl propionate, ethyl acetate, γ-butyrolactone, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, dimethoxymethane, 1,2-dimethoxypropane, triethylene glycol dimethyl ether, dimethyl sulfone, dimethyl ether, vinyl sulfite, propylene sulfite, and dimethyl sulfite. One or more.
[0059] In some embodiments of the present invention, the solvent is a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC).
[0060] In some embodiments of the present invention, the volume ratio of EC, EMC and DEC in the solvent is (0.5-2):(0.5-2):1.
[0061] In some embodiments of the present invention, the volume ratio of EC, EMC and DEC in the solvent is (0.5-1.5):(0.5-1.5):1.
[0062] In some embodiments of the present invention, the volume ratio of EC, EMC and DEC in the solvent is 1:1:1.
[0063] In some embodiments of the present invention, the secondary battery further includes a separator.
[0064] In some embodiments of the present invention, the separator may be a separator commonly used in the art, such as a polyethylene (PE) separator, a polypropylene (PP) separator or a PE / PP composite separator, preferably a PE separator.
[0065] A fifth aspect of the present invention provides an electrical device, which includes the secondary battery described above.
[0066] Specifically, the secondary battery proposed in the present invention has excellent fast charging performance and good high temperature performance. The fast charging performance enables the battery to be quickly charged in a short time, thereby improving the practicality of electrical devices; the high temperature performance ensures that the battery will not be damaged due to overheating during fast charging. While fast charging, the safety and stability of the battery are guaranteed.
[0067] In some embodiments of the present invention, the power-consuming device is an electric vehicle, or other power-consuming devices such as energy storage systems, electric tools, drones, mobile devices such as wearable products, laptops, mobile phones, etc.
[0068] In some embodiments of the present invention, the electric vehicle comprises an electric bicycle, an electric motorcycle, an electric bus, an electric truck or an electric rail car.
[0069] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0070] (1) The negative electrode material proposed in the present invention contains a graphite core and a composite carbon coating layer composed of graphitized carbon and hard carbon. The presence of hard carbon in the composite carbon coating increases the active sites on the surface of the material for lithium ion embedding, thereby improving the fast charging performance of the material. The ordered graphitized carbon and disordered hard carbon in the composite carbon coating are evenly distributed, which provides more lithium embedding active sites on the graphite surface and effectively reduces the deterioration of the high-temperature performance of the material.
[0071] (2) In the preparation process of the negative electrode material proposed in the present invention, epoxy asphalt is used as the coating agent raw material, and the resin-based component and asphalt component coexisting in the epoxy asphalt are utilized. After carbonization and graphitization treatment, a uniformly distributed hard carbon and graphitized carbon composite carbon coating layer is obtained. Compared with the coating of hard carbon or soft carbon, the material is endowed with more excellent fast charging performance and high temperature performance.
[0072] (3) The negative electrode material proposed in the present invention is applied to lithium-ion batteries, and its kinetic performance test shows that there is no lithium deposition or slight lithium deposition, and it has excellent fast charging performance; the capacity recovery rate after 100 days of high-temperature storage at 60°C can reach 80.3-91.9%, and it has good high-temperature performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0074] Figure 1 Schematic diagram of the structure of the negative electrode material prepared in an embodiment of the present invention.
[0075] Wherein: 100 represents the graphite core; 200 represents the composite carbon coating layer. DETAILED DESCRIPTION
[0076] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be reagents and materials obtained from commercial channels. Unless otherwise specified, the same parameter in each embodiment has the same value. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention.
[0077] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0078] Example 1
[0079] A method for preparing a composite carbon-coated graphite negative electrode material comprises the following steps:
[0080] (1) mixing artificial graphite and water-based epoxy asphalt in a mass ratio of 10:1 in a drum mixer at a speed of 3000 rpm for 1 hour to obtain a mixture;
[0081] (2) subjecting the mixture obtained in step (1) to a high-temperature carbonization treatment at 1200° C. for 2 hours in a nitrogen atmosphere to obtain carbon-coated graphite;
[0082] (3) The carbon-coated graphite obtained in step (2) is subjected to high-temperature graphitization treatment at 3000° C. in an argon atmosphere for 4 hours to obtain a composite carbon-coated graphite negative electrode material.
[0083] The structural schematic diagram of the composite carbon-coated graphite negative electrode material prepared in this embodiment is shown in Figure 1 As shown, the negative electrode material includes a graphite core 100 and a composite carbon coating layer 200. The composite carbon coating layer 200 is composed of graphitized carbon and hard carbon, and the graphitized carbon and the hard carbon are evenly distributed.
[0084] The structures of the negative electrode materials prepared in other embodiments are similar to those in Embodiment 1 and are not shown one by one to avoid redundancy.
[0085] Examples 2-12 and Comparative Examples 1-4
[0086] The difference between the preparation methods of the negative electrode materials of Examples 2-12 and Comparative Examples 1-4 and Example 1 is that the raw material selection of the coating agent epoxy asphalt, the mass ratio of artificial graphite to the coating agent, or the graphitization treatment temperature and time are different, as shown in Table 1.
[0087] Table 1:
[0088]
[0089]
[0090] Comparative Example 5
[0091] The preparation method of the negative electrode material of Comparative Example 5 is different from that of Example 1 in that: in step (1), epoxy asphalt is replaced with phenolic resin and coal tar pitch. Specifically: (1) artificial graphite, phenolic resin and coal tar pitch are mixed in a drum mixer at a mass ratio of 10:0.5:0.5 at a rate of 3000 rpm for 1 hour to obtain a mixture.
[0092] The remaining preparation steps are the same as those in Example 1 and will not be described again here.
[0093] Application Examples
[0094] The graphite negative electrode materials prepared in the above examples 1-12 and comparative examples 1-5 are respectively used as the active materials of the negative electrode plates to prepare lithium ion batteries, and the specific steps are as follows:
[0095] (1) Preparation of positive electrode sheet
[0096] The positive electrode active material NCM523, the conductive agent carbon nanotubes, and the binder PVDF are mixed in a mass ratio of 93:3:4, and the solvent NMP is added, and the mixture is stirred evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on both sides of the positive electrode collector aluminum foil, dried in an oven, and then cold pressed and cut to obtain a positive electrode sheet.
[0097] (2) Preparation of negative electrode sheet
[0098] First, prepare the negative electrode slurry, in which the ratio of composite carbon coated graphite, conductive carbon black, CMC, and SBR is 93:3:2:4, and the solid content of SBR is 50%. The specific preparation method of the negative electrode slurry is as follows: add deionized water, conductive carbon black and 70% CMC powder to a stirring tank, stir at low speed for 2 hours to form a conductive glue; then add composite carbon coated graphite to the conductive glue, stir at low viscosity and high speed for 1 hour to form a first mixed solution; then add SBR to the first mixed solution, stir at high viscosity and high speed for 1 hour to form a second mixed solution; finally, add ethanol and the remaining 30% CMC powder to the second mixed solution, stir at low viscosity and high speed for 2 hours to prepare the negative electrode slurry, and the ratio of deionized water to ethanol in the slurry is 9:1. The negative electrode slurry is evenly coated on both sides of the negative electrode current collector copper foil, dried in an oven, and then cold pressed and cut to obtain the negative electrode sheet.
[0099] (3) Preparation of electrolyte
[0100] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a concentration of 1 mol / L to obtain an electrolyte after full dissolution.
[0101] (4) Preparation of isolation membrane
[0102] A polyethylene film was selected as the separator.
[0103] (5) Preparation of lithium-ion batteries
[0104] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0105] Performance Testing
[0106] The lithium-ion battery prepared in the above application example was subjected to a kinetic performance test and a high-temperature storage performance test, and the ratio of ID / IG in the composite carbon coating layer was tested using Raman spectroscopy. The test process is as follows:
[0107] (1) Dynamic performance test: At 25°C, a lithium-ion battery made of the negative electrode materials prepared in Examples 1-12 and Comparative Examples 1-5 as the active material of the negative electrode plate was fully charged at a 4C rate and fully discharged at a 1C rate for 10 times, and then the lithium-ion battery was fully charged at a 4C rate, and then the negative electrode plate was disassembled and the lithium deposition on the surface of the negative electrode plate was observed. Among them, the area of lithium deposition on the surface of the negative electrode plate is less than 5%, which is considered to be slight lithium deposition, the area of lithium deposition on the surface of the negative electrode plate is 5-40%, which is considered to be moderate lithium deposition, and the area of lithium deposition on the surface of the negative electrode plate is greater than 40%, which is considered to be severe lithium deposition.
[0108] (2) High temperature storage test: At 25°C, a lithium ion battery made of the negative electrode material prepared in Examples 1-12 and Comparative Examples 1-5 as the active material of the negative electrode plate was fully charged at a rate of 0.33C and fully discharged at a rate of 0.33C. A capacity test was performed and the discharge capacity 1 of the battery cell was recorded. The lithium ion battery was then fully charged at a rate of 0.33C and transferred to a 60°C oven for 100 days. After 100 days, the lithium ion battery was taken out and re-capacitated at a rate of 0.33C and the discharge capacity 2 of the battery cell was recorded. The 60°C storage capacity recovery rate of the battery cell can be obtained by recording the ratio of the discharge capacity 2 to the discharge capacity 1.
[0109] The test results are shown in Table 2.
[0110] Table 2:
[0111] ID / IG Dynamic performance Capacity recovery rate after 100 days storage at 60℃ (%) Example 1 0.33 No lithium precipitation 89.7 Example 2 0.34 Slight lithium deposition 91.9 Example 3 0.34 No lithium precipitation 86.4 Example 4 0.32 No lithium precipitation 84.1 Example 5 0.68 No lithium precipitation 80.3 Example 6 0.58 No lithium precipitation 82.2 Example 7 0.41 No lithium precipitation 87.5 Example 8 0.38 No lithium precipitation 88.3 Example 9 0.31 No lithium precipitation 90.6 Example 10 0.37 No lithium precipitation 87.8 Embodiment 11 0.31 No lithium precipitation 90.7 Example 12 0.3 No lithium precipitation 90.9 Comparative Example 1 0.86 No lithium precipitation 72.3 Comparative Example 2 0.03 Severe lithium deposition 94.4 Comparative Example 3 3.22 No lithium precipitation 76.8 Comparative Example 4 0.74 No lithium precipitation 80.2 Comparative Example 5 0.97 Slight lithium deposition 81.4
[0112] It can be seen from Table 2 that the coating thickness has a great influence on the fast charging performance and high temperature storage performance of the composite carbon-coated graphite negative electrode material. When the coating layer is too thin, the proportion of hard carbon components in the composite carbon-coated graphite is too small, and there are fewer active sites on the surface of the material for lithium ion embedding, and the fast charging performance is poor. The kinetic performance test result of Example 2 is slight lithium precipitation, which is slightly worse than Example 1. When the coating layer is too thick, the proportion of hard carbon components in the composite carbon-coated graphite is too large, and there are more side reactions between the composite carbon-coated graphite and the electrolyte under high temperature conditions, and the high temperature storage performance is poor. The capacity recovery rate of Comparative Example 1 stored at 60°C for 100 days is only 72.3%.
[0113] When there are too few hard carbon components in the composite carbon coating layer and too many graphitized carbon components, resulting in the intensity ratio ID / IG of the Raman D peak to the G peak of the composite carbon coating layer being lower than 0.15, the fast charging performance of the material is poor. This is because when there are too few hard carbon components in the coating layer, there are too few active sites on the surface of the material for lithium ions to embed, and the charge transfer of lithium ions on the surface of the material is limited. Under high-rate charging conditions, lithium ions tend to aggregate on the surface of the material and generate lithium dendrites, resulting in poor fast charging performance of the battery. The kinetic performance test results of Comparative Example 2 show severe lithium precipitation.
[0114] When there are too many hard carbon components in the composite carbon coating and too few graphitized carbon components, resulting in the intensity ratio ID / IG of the Raman D peak to G peak of the composite carbon coating being higher than 0.7, the high temperature performance of the material is poor. This is because when there are too many hard carbon components in the coating, there are more exposed end faces and defects on the surface of the material, which are prone to more side reactions with the electrolyte and generate impurities under high temperature conditions, resulting in irreversible capacity loss of the battery. The capacity recovery rate of Comparative Example 3 after 100 days of storage at 60°C is only 76.8%, and the capacity recovery rate of Comparative Example 4 after 100 days of storage at 60°C is only 80.2%.
[0115] When phenolic resin and coal tar pitch are replaced with epoxy pitch, although the coating layer also contains hard carbon and graphitized carbon after high-temperature carbonization and graphitization, due to the poor compatibility of phenolic resin and coal tar pitch, it is difficult to achieve homogenization under conventional mixing conditions, resulting in unsatisfactory dynamic performance and high temperature resistance of the material. The capacity recovery rate of comparative example 5 after storage at 60°C for 100 days is only 81.4%.
[0116] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A negative electrode material, characterized in that: The negative electrode material comprises a core and a coating layer coated on the outer surface of the core, the core comprises graphite, the coating layer comprises graphitized carbon and hard carbon, and the graphitized carbon and hard carbon are evenly distributed.
2. The negative electrode material according to claim 1, characterized in that The intensity ratio of the Raman D peak and the Raman G peak of the coating layer satisfies the relationship of ID / IG: 0.15≤ID / IG≤0.
7.
3. The negative electrode material according to claim 1 or 2, characterized in that: The graphite is selected from one or more of artificial graphite, flake graphite, earthy graphite, and mesophase carbon microspheres.
4. A method for preparing a negative electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing graphite and epoxy asphalt to obtain a mixture; (2) subjecting the mixture obtained in step (1) to carbonization treatment in an inert atmosphere to obtain carbon-coated graphite; (3) The carbon-coated graphite obtained in step (2) is graphitized in an inert atmosphere to obtain the negative electrode material.
5. The method for preparing the negative electrode material according to claim 4, characterized in that: In step (1), the epoxy asphalt is selected from one or more of water-based epoxy asphalt, cured asphalt, and solvent-free epoxy asphalt; and / or the mass ratio of the graphite to the epoxy asphalt is 10:(0.5-3).
6. The method for preparing the negative electrode material according to claim 4, characterized in that: In step (2), the temperature of the carbonization treatment is 700-1500° C.; and / or the time of the carbonization treatment is 1-4 hours.
7. The method for preparing the negative electrode material according to claim 4, characterized in that: In step (3), the temperature of the graphitization treatment is 2600-3200° C.; and / or the time of the graphitization treatment is 2-12 hours.
8. A negative electrode plate, characterized in that: The raw material for preparing the negative electrode plate includes the negative electrode material as described in any one of claims 1 to 3, or includes the negative electrode material prepared by the preparation method as described in any one of claims 4 to 7.
9. A secondary battery, characterized in that: The secondary battery comprises the negative electrode sheet as claimed in claim 8.
10. An electrical device, characterized in that: The electric device comprises the secondary battery as claimed in claim 9.
Citation Information
Cited By
Negative electrode active material and preparation method therefor, negative electrode sheet, battery, and electric device
WO2026194905A1